REVITALIZATION OF BADAN PENASIHATAN, PEMBINAAN DAN PELESTARIAN PERKAWINAN (BP4) IN PERFORMING COURT-ANNEXED MEDIATION FOR MARITAL DISPUTES IN RELIGIOUS COURT IN D.I.YOGYAKARTA - Haniah Ilhami (Mimbar Hukum - Fakultas Hukum Universitas Gadjah Mada, 2017)
This research identify the revitalization of Badan Penasihatan, Pembinaan dan Pelestarian Perkawinan (BP4) after The 14th BP4 National Conference in 2009, in performing Court-annexed mediation for Marital Dispute at Religious Court in D.I. Yogyakarta. This  research founds several institutional transformation of BP4 including the Legal Basis, Institutional Form, Institutional Relation with Ministry of Religious Affair, Employement/Management Provisions, and Financial Provisions. In Performing Court-annexed mediation. BP4 in D.I. Yogyakarta has been cooperating with 2 (two) Religious Courts, both in Wonosari and Yogyakarta through Memorandum of Understanding in form of cooperation in the placement of certified mediator from BP4 and cooperation in funding the certified mediators. All Mediators are bound by Regulation of The Supreme Court No. 1 year 2016 concerning Procedures of Court-annexed Mediation, related to Types  of  Cases  Mediated,  Mediator’s  Fee,  Venue  of  Mediation,  Period  of  Mediation,  and Mediator’s requirement.